نظرية في مسلك التفسير الأمثل لآيات القرآن الكريم: دراسة تأصيلية لمنهج تكاملي في تفسير القرآن الكريم - بني كنانة، مجتبى بن محمود بن عقلة (جامعة الأزهر - كلية اصول الدين والدعوة باسيوط, 2021)
موضوع هذه الدراسة نتاج نظرة شمولية لتفسير القرآن المعاصر والتراثي؛ حيث تنوع تناول المفسرين لتفسير القرآن الكريم، واتسع في هذا العصر الإنتاج التفسيري بما يسع له المسلك الفكري الإنساني، مبتعدا عن مفهوم التفسير وضوابطه المستمدة من المسلك الأصولي. وتهدف هذه الدراسة إلى صياغة نظرية متكاملة لمسلك التفسير الأمثل لآيات القرآن الكريم، منطلقة من مفهوم منضبط للتفسير. وسلك البحث لتحقيق أهدافه المنهج: الوصفي والتحليلي والنقدي والاستنباطي، فاستحضر الواقع التفسيري بإجمال، ومن خلال تحليل النتاج التفسيري أظهر بنقده الحاجة إلى نظرية لمسلك أمثل في التفسير، صاغتها الدراسة وبينت أركانها وأجرت عليها دراسة تطبيقية لبيان ميزتها وأثرها. وأهم النتائج: أولا: نظرية التفسير هي: المقارنة بين مسالك التفسير الموروث والمعاصر، ودراستها ونقدها وبيان آثارها على القرآن وغايته، وعلى غيرها من العلوم، للوصول لمسلك التفسير الأمثل؛ الذي عرفته الدراسة: بأنه: إرادة تفسير القرآن بما يفتح الله به ويوفق المفسر له، لكنه مراده سبحانه من آياته؛ لفهمها وإفهامها، دون تجاوز نظمها مفردة ومجمعة، وبيان السنة المتسق معها، لغاية القرآن من الهداية أو الغواية، لا لغاية المفسر ولو كانت صحيحة، مع الالتزام التام بكل ذلك. ثانيا: أركان هذه النظرية هي: التقيد بالمفهوم القرآني للتفسير، واتباع منهج النبي- صلى الله عليه وسلم-، واستحضار السياق التاريخي، وتتبع نظم القرآن الكريم ومستوياته. ونظم القرآن يتضمن سبعة مستويات يفسر القرآن بها في التفسير الأمثل وهي: المستوى: الصوتي والصرفي والمعجمي والنحوي البلاغي والساقي والدلالي والفكري.
The topic of this study is the result of a comprehensive view of the contemporary and traditional interpretation of the Qur’an where the interpretators dealing with the interpretation of the Noble Qur’an was diversified, and expository of interpretation production expanded in this era to accommodate the human intellectual path, moving away from the concept of interpretation and its restrictions derived from the fundamentalist approach. This study aims to formulate an integrated theory of the path of optimal interpretation of the verses of the Noble Qur’an, based on a disciplined concept of interpretation. The research adopted the descriptive, analytical, critical, and deductive approach to achieve its goals. He summarized the interpretative reality in general, and through the analysis of the interpretative product, he demonstrated, with his criticism, the need for a theory for an optimal course of interpretation, formulated by the study, showing its pillars, and conducting an applied study to demonstrate its advantage and impact. The most important results: First: The theory of interpretation is a comparison between the paths of inherited and contemporary interpretation, studying and criticizing them, stating their effects on the Qur’an and its purpose, and on other sciences to reach the path of optimal interpretation; which the study defined that it is the desire to interpret the Qur’an by what God inspires and sustains the interpreter with, but what He wants is the interpretation of His verses to understand and simplify it without going beyond its singular and collective systems, and the statement of the Sunnah consistent with it, for the purpose of the Qur’an from guidance or misguidance, not to the purpose of the interpreter even if it is correct, with full commitment to all of that. Second is the pillars of this theory are adherence to the Qur’an concept of interpretation, following the approach of the Prophet, evoking the historical context, and following the systems and levels of the Holy Qur’an. And the systems of the Qur’an include seven levels. The Qur’an is interpreted in the ideal interpretation, namely: The phonemic, morphological, lexical, rhetorical, contextual, semantic and intellectual grammar.
Keywords: القرآن الكريم -- التفسيرات القرآنية -- علم البلاغة